2016
DOI: 10.15578/squalen.v11i2.213
|View full text |Cite
|
Sign up to set email alerts
|

Internal Transcribed Spacer (ITS) as Dna Barcoding to Identify Fungal Species: a Review

Abstract: Despite the fact that fungi are important sources of both bioactive compounds and mycotoxins, and that they are very ubiquitous in our environment, their species identification is hampered by incomplete and often unclear literature. Fungi identification is primarily based on their phenotypic and physiological characteristics. Nowadays, many molecular methods to identify fungal species have been developed. One of the methods considered as a new concept to rapidly and accurately identify unknown fungal sample is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
(34 reference statements)
1
15
0
1
Order By: Relevance
“…The region from which the primer is designed should be conserved and unique to the target species [16]. The ITS region is very useful in identifying fungi at species level hence it is the primary barcode for the fungal kingdom [22]. That explains why in this study, the ITS1, 5.8S, ITS2 and partial sequence of the large subunit ribosomal RNA in the genome of P. angolensis were used to design both PCR and LAMP primers.…”
Section: Discussionmentioning
confidence: 99%
“…The region from which the primer is designed should be conserved and unique to the target species [16]. The ITS region is very useful in identifying fungi at species level hence it is the primary barcode for the fungal kingdom [22]. That explains why in this study, the ITS1, 5.8S, ITS2 and partial sequence of the large subunit ribosomal RNA in the genome of P. angolensis were used to design both PCR and LAMP primers.…”
Section: Discussionmentioning
confidence: 99%
“…In fungi, ITS1 and ITS2 are located in the rDNA gene complex between the 18s and 5.8s rRNA and 5.8s and 26s rRNA genes respectively (32). These regions are distinguished by their variations among fungal species and have therefore been selected as DNA barcode to differentiate the fungal species (33). Leaw et al, have demonstrated the candidate ITS regions for Candida species identification.…”
Section: Molecular Identification Of Candida Polymerase Chain Reactiomentioning
confidence: 99%
“…This method serves the rapid identification of fungi and other organism at species level. The ITS region is the most widely sequenced region in DNA used for the identification of fungi (22) and has been recommended as the universal fungal barcode sequence (23).…”
Section: Introductionmentioning
confidence: 99%